PROSES MANJEMEN, STRUKTUR FORMAL DAN PENGGUNAAN INFORMASI - Meutia, Meutia (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
The purpose of this paper is to research whether activity of strategy development and implementation used in practice are formal structured processes, and whether financial and non-financial information are of equal importance across strategy development and implementation activities. This study uses senior accounting officers within large Banten and West Java firms (those employing more than 250 employees). The result from hypotheses testing showed that that strategy development and implementation were relatively formally structured processes in the companies investigated. Nevertheless, financial information and non-financial information are considered equally important both for the development of the strategy and implementation of strategies for the companies surveyed. Companies, it provides value and weight as important both to the financial information for strategy implementation process.